Effect of Smoking on Chest Expansion, Respiratory and Lung Functions - Jagdesh Kumar, Shafi Muhammad Khuhawar, Bashir Ahmed Chandio, Khalil Ahmed Sanghro, Saleh Muhammad Channa, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To highlight the effect of smoking on chest expansion, respiratory and lung functions. Study Design: Case control study. Place and Duration of Study: Department of Pulmonology, Ghulam Muhammad Mahar Medical College, Sukkur from 1st June 2021 to 30th November 2021. Methodology: One hundred and fifty individuals were enrolled. Interviews were taken in form of focal group discussion from each smoker (n=100) and non-smoker (n=50) participants about smoking history and their clinical pulmonary systems. Age of smoking, average consumption of cigarette was also some of the questions asked and responses were documented from smokers. Respiratory lung function test was conducted in all of the individuals using chest expansion and lung function test was performed in all individuals using spirometry and respiratory-muscle test. The spirometry measurements were calculated through forced expiratory volume calculation within 1st second (FEV1) and the vital capacity (FVC) and FEV1/FVC ratio. All measurements were taken as average of three trials. Results: Majority of the study participants were in the age group of 13-25 years. Highest frequency of smoking was observed within 1-3year. Majority of the smokers (48%) were taking ≤10 cigarettes in a day. Low nicotine dependence was observed in 90% of the smokers. Conclusion: Majority of the participants were taking ≤10 cigarettes in a day. Chest expansion was considerably higher in smokers as compared to non-smokers.